Equity Trading by Institutional Investors: Evidence on Order Submission Strategies - Randi Næs; Johannes A. Skjeltorp (Norges Bank, 2002)
The trading volume channeled through off-market crossing networks is growing. Passive matching of orders outside the primary market lowers several components of execution costs compared to regular trading. On the other hand, the risk of non-execution imposes opportunity costs, and the inherent "free riding" on the price discovery process raises concerns that this eventually will lead to lower liquidity in the primary market. Using a detailed data set from a large investor in the US equity markets, we find evidence that competition from crossing networks is concentrated in the most liquid stocks in a sample of the largest companies in the US. Simulations of alternative trading strategies indicate that the investor's strategy of initially trying to cross all stocks was cost effective: in spite of their high liquidity, the crossed stocks would have been unlikely to achieve at lower execution costs in the open market.
hdl:11250/2498661
Keywords: G10; G20; 330; costs of equity trading; crossing; limit order trading; institutional equity trading